The consumer in the Polish organic food market. A Siedlce example - Nowogródzka, Teresa (Management and Administration Journal, 2019)
This paper deals with consumer attitude and behaviour towards organic food. Among otherthings, it presents a profile of organic food consumers together with an attempt to differentiate themaccording to their preferences for organic food. The paper also discusses food labelling which makesit possible for the customer to get information about whether a particular item of food is organic or not.